Belgian observational survival data (incidence years 2004–2017) and expenditure for innovative oncology drugs in twelve cancer indications. (March 2023) - Neyt, Mattias; Devos, Carl; Thiry, Nancy; Silversmit, Geert; De Gendt, Cindy; Van Damme, Nancy; Castanares-Zapatero, Diego; Hulstaert, Frank; Verleye, Leen
Abstract: Background: The Food and Drug Administration and European Medicines Agency typically approve market access for cancer drugs based on surrogate end-points, which do not always translate into substantiated improvements in outcomes that matter the most to patients, i.e. survival and quality of life. These drugs often, also, have a high price tag. We assessed whether there was an increase in cancer drug expenditure for a broad selection of indications, and whether this correlates with increased overall survival. Methods: This cohort study used Belgian Cancer Registry data from 125, 692 patients (12 cancer indications, incidence period 2004–2017), which was linked to reimbursement and survival data. This reliably represents the Belgian situation. One-to-five year observed survival probability, median survival time, oncology drug expenditure and mean oncology drug cost per patient were reviewed. Findings: In almost all indications, total expenditure and average treatment cost for oncology drugs increased over the years (2004–2017). In contrast, mixed findings are observed for the evolution in overall survival probability and median survival time. While an absolute improvement in the 3-year survival probability of about 10% is noticed in non-small-cell lung cancer and chronic myeloid leukaemia, improvements in about half of the other indications are limited or even absent. Interpretation: The Belgian observational data indicate that assuming 'innovative' oncology drugs always add value in terms of improved survival is often unjustified. The literature also highlights the problem of using surrogate end-points, and the lack of comparative evidence showing an added value of oncology drugs for both survival and quality of life at market approval or during the post-marketing phase. Comparative studies should be conducted in the pre-marketing phase that are suitable for registration purposes, aid reimbursement decisions and support physicians and patients when making treatment decisions. Highlights: Food and Drug Administration and European Medicines Agency typically approve cancer drugs based on surrogate end-points. Overall survival (OS) and quality of life data are often not available to decision makers. Evolution in OS and drug expenditure (12 cancer types, 125 692 patients) is described. Substantial increases in drug expenditure often do not coincide with clear OS gains. Comparative pre-marketing studies should include OS and quality of life as patient-relevant outcomes.